PENERAPAN PENDEKATAN CTL DENGAN MEDIA BENDA KONKRET DALAM PENINGKATAN PEMBELAJARAN IPA SISWA KELAS V SDN PATEMON TAHUN AJARAN 2012/2013 - nugraeni, dwi nuni (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Application of CTL approach by Using Concrete Objects in Science Student Learning Improvement 5TH Grade SDN Patemon in Academic Year 2012/2013. This study aimed to describe:(1) the implementation of CTL approach with concrete objects in an increase in media science,(2) constraints and applications solutions CTL approach with concrete objects media in increasing students learning science. Fifth grade students of SDN Patemon consist of 30 students. This research is a classroom action research was conducted in three cycles, each cycle consists of planning, implementation, observation and reflection. Data collecting methods are collected through observation, interview, test, and documentation. The validity of data using the source triangulation. The data Analysis is used by this research in kuantitatif and kualitatif data analysis. Results of this study indicate that the application of this approach to media CTL concrete objects can improve science teaching fifth grade students of SDN Patemon Academic Year 2012/2013. Keywords: CTL Approach, Concrete Media Objects, Learning Science   Abstrak: Penerapan Pendekatan CTL dengan Media Benda Konkret Dalam Peningkatan   Pembelajaran IPA Siswa Kelas V SDN Patemon Tahun Ajaran 2012/2013. Penelitian ini bertujuan untuk mendeskripsikan: (1) penerapan pendekatan CTL dengan media benda konkret dalam peningkatan pembelajaran IPA, (2) kendala dan solusi penerapan pendekatan CTL dengan media benda konkret dalam peningkatan pembelajaran IPA. Subjek penelitian siswa kelas V SDN Patemon sejumlah 30 siswa. Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan dalam tiga siklus, tiap siklus terdiri atas perencanaan, pelaksanaan, observasi dan refleksi. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, tes, dan dokumentasi. Validitas data menggunakan metode triangulasi. Analisis data yang digunakan adalah analisis kualitatif dan kuantitatif. Hasil penelitian ini menunjukkan bahwa dengan penerapan pendekatan CTL dengan media benda konkret dapat meningkatkan pembelajaran IPA siswa kelas V SDN Patemon Tahun Ajaran 2012/2013.   Kata Kunci: Pendekatan CTL, Media Benda Konkret, Pembelajaran IPA